Evaluation of natural radioactivity and hazard indices in the soil collected from the residential college areas of University Malaya, Malaysia / Okereafor Casmir Nneji - Okereafor Casmir , Nneji (2017)
Realizing the heterogeneous distribution of naturally occurring radioactive materials (NORM) in all earth born media, it is important to assess their concentrations in residential hostels environment to control the occupants’ health from radiation exposure. In connection with this, soil samples collected from all residential colleges of University of Malaya were assessed to obtain the concentrations of NORM by using HPGe gamma-ray spectrometry. The activity concentrations of 226-Ra ranged from 42.16 to 61.27 Bq/kg, 232-Th ranged from 52.89 to 81.80 Bq/kg and 40-K ranged from 73.07 to 306.43 Bq/kg. Radium-226, Thorium-232 and Potassium-40 have average activity concentration of 52.31±2.40 Bq/kg, 68.42±1.92Bq/kg and 224.58±2.28Bq/kg respectively. The results show that the average concentrations of the primordial radionuclides were lower than Malaysia average values. But 232-Th and 226-Ra are higher than the world average while 40-K is lower compared with values giving in UNSCEAR 2000. The dose rate and radiological indices were obtained and compared with worldwide recommended values